Projekty na snižování nezaměstnanosti, na nichž spolupracuje Úřad práce ve Svitavách - Kosinová, Iva (Univerzita Pardubice, 2006)
Tato práce se věnuje projektům, které jsou realizovány, aby pomohly snížit nezaměstnanost určitých skupin uchazečů o zaměstnání. První analyzovaný projekt je určen ke zlepšení zaměstnávání mladistvých a absolventů (tj. osob do 25 let), matek s dětmi do 15 let a uchazečů nad 50 let. Druhý v práci analyzovaný projekt je určen pro zaměstnavatele, kteří zaměstnávají větší počet zdravotně postižených občanů.

This bachelor paper deals with projects realized to help decrease unemployment rate of certain groups of aplicants. The first analyzed project is devoted to improvement of employing youths and graduates (i.e. persons under age 25), mothers with children under age 15, and the aplicants above age 50. The second project analyzed at work focuses on employers providing jobs for a high number of disabled people.
Unemployment rate decrease projects collaborated by the Work office in Svitavy
Keywords: active politics; Employment; Unemployment; MPSV projects; Disabled people; aktivní politika; zaměstnanost; Nezaměstnanost; projekty MPSV; zdravotně postižení lidé